Evaluation of the structural and functional state of the thigh muscles in patients with femoral fracture outcomes according to ultrasound. - Sokol, V. K. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. With fractures of the femur, muscle damage occurs, which, in conditions of delayed consolidation of the fracture or accrete fracture with residual adverse displacement, as well as inadequate rehabilitation in the postoperative period, can lead to a decrease in support function with the development of long-term or permanent disability and the outcome of this injury grievous bodily harm. Objective. The goal is to investigate the structural and functional characteristics of the thigh muscles in the event of the effects of fractures. Methods. The material of the study is the protocols of clinical and radiological examination of 18 patients with accrete closed femoral diaphysis fractures with residual deformities, in which, as a result of the initial expert assessment, the severity of injuries due to the development of postoperative complications was not established. The methods of the study are clinical, radiological, ultrasound (US) of the biceps femoris, the rectus femoris, the wide medial and the wide lateral muscles. Results. According to the results of the ultrasound, the contour of the studied muscles was clear and even on both limbs; The echogenicity of the muscles of the affected limb was increased in all the examined, the structure was sometimes heterogeneous. On the affected limb, at the first examination at rest, a decrease in the thickness of the muscles studied was revealed, more pronounced on m.vastus medialis and m.vastus lateralis. The greatest decrease in contractility was observed on m.rectus femoris and m.vastus lateralis, which was almost 6.0; 6.6% of the possible reduction of intact muscle. The results of the second study after the load showed an increase in KSp2, characterizing the degree of violation of contractile properties: for m.rectus femoris - by 20.0%, for m.biceps femoris - by 28.9%, for m.vastus medialis - by 34.9 %, for m.vastus lateralis - by 21.2%. Conclusion. A tendency to a decrease in muscle tissue thickness, a violation of its structure, an increase in echogenicity during ultrasound at rest and a clear tendency to a decrease in contractility of all investigated muscles according to the results of functional testing of muscle properties of injured lower limb in patients with femoral fractures with residual deformities diaphysis.